Knowledge, Attitudes, and Practices of Chinese Breast Cancer Patients Towards Comprehensive Postoperative Self-Management: a Cross-Sectional Study - Wei X; Ye P; Chen L; Tang H; Yin W; Shao M; Bai R; Li Y; Yu J; Wang W; Zhang J (Journal of Multidisciplinary Healthcare)
Xiaoyu Wei,1,* Ping Ye,2,* Lingling Chen,3 Huiqin Tang,1 Weiwei Yin,4 Min Shao,5 Ru Bai,6 Yun Li,5 Jiya Yu,7 Wei Wang,5 Jing Zhang8 1Department of Operating Room, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China; 2Department of Gynecologic Oncology, The First Affiliated Hospital of Bengbu Medical University, Bengbu, 233004, People’s Republic of China; 3Department of Nursing, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China; 4Department of Thoracic Surgery, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China; 5Department of Oncological surgery, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China; 6Department of Oncological surgery, The First Affiliated Hospital of Bengbu Medical University, Bengbu, 233004, People’s Republic of China; 7Department of Nursing, Bengbu Medical University, Bengbu, 233030, People’s Republic of China; 8Department of Mental Health, Bengbu Medical University, Bengbu, 233030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingling Chen, Department of Nursing, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China, Tel +86-13909629122, Email 1314chenlingling@163.com Jing Zhang, Department of Mental Health, Bengbu Medical University, Bengbu, 233030, People’s Republic of China, Tel +86-13505522198, Email 0700007@bbmc.edu.cnPurpose: To comprehensively assess the knowledge, attitudes, and practices (KAP) of Chinese breast cancer (BC) patients regarding postoperative self-management (POSM) and identify factors influencing self-management behaviors.Methods: Questionnaire surveys were administered to BC patients who underwent surgery. A total of 566 participants (98.94% female), mainly from rural areas (65.55%) and married (97.53%), were included. Knowledge was measured using 10 questions (score range: 0– 20), attitude with 6 questions (score range: 6– 30), and practice with 7 questions (score range: 6– 30). Scores were categorized as inadequate (0%– 39.99%), moderate (40%– 70%), or satisfactory (> 70% of maximum score). Demographic data were collected, and statistical analyses, including T-tests, ANOVA, non-parametric tests, and Spearman correlation, were used for comparisons and associations.Results: The average knowledge score was 20.00 (100% of the maximum score), with correct answer rates ranging from 92.58% to 99.29%. Attitude scores averaged 29.00 (96.66% of maximum), with 95.93– 98.76% of participants showing positive or very positive attitudes. The average practice score was 26.00 (86.66% of maximum), with notable gaps in seeking psychological support (28.27% negative responses) and lifestyle adjustments (41.34% negative responses). Pearson correlation analysis revealed positive associations between knowledge and attitude (r = 0.227, p < 0.001), and attitude and practice (r = 0.111, p = 0.008). Multivariable analysis found homemakers showed better practices compared to employed individuals (OR = 9.667, 95% CI = 2.483– 37.643, p = 0.001), while those with “other” employment status had lower odds of practice (OR = 0.437, 95% CI = 0.206– 0.927, p = 0.031). Patients with Stage II or III tumors had lower odds of practice compared to Stage I tumors (OR = 0.273, 95% CI = 0.110– 0.677, p = 0.005; OR = 0.157, 95% CI = 0.060– 0.410, p < 0.001, respectively).Conclusion: This study highlights the importance of addressing gaps between knowledge, attitudes, and practices in BC patients undergoing postoperative recovery. Tailored interventions focusing on specific barriers identified in practice behaviors, such as seeking psychological support and lifestyle adjustments, are crucial to enhance overall postoperative care and improve health outcomes for BC patients.Keywords: breast cancer, knowledge, attitude, practice, postoperative self-management